Innovation in Realistic Animated Fairy Tale Video Learning Media for Children Aged 5–6 Years: An Effort to Improve Language Skills: English - Nuni, Wahyuningsih; Gatot, Masitowati (Educational Researcher Journal, 2025)
This study aims to develop learning media in the form of realistic animated fairy tale videos based on storytelling methods to improve the language skills of early childhood group B at Garuda Yaksa Kindergarten, Bogor Regency. Based on the low language skills of children, as indicated by initial data that 53% of children are in the category of Not Yet Developing, 27% Starting to Develop and only 20% Developing as Expected. The method used in this study is Research and Development (R&D) by combining the Lee and Owens model and the ASSURE model. The media development process includes needs analysis, media design, animated video production, validation by experts (materials, media, and instructional design) as well as limited and extensive trials. The results of the study indicate that the developed realistic animated fairy tale video media is effective in improving children's language skills. This is proven by a comparison of the pretest and posttest results in three cycles of testing the N-Gain score assessment categorization with a final score of 86% where there is a significant increase in the learning outcome score. In addition, this media is also able to increase children's interest and active participation during the learning process. The conclusion of this study is that realistic animated fairy tale video learning media based on storytelling has proven to be feasible and effective as an alternative solution in creating an interesting, interactive and meaningful learning process for early childhood, especially in improving language skills in the digital era.